ANALYSIS OF THE SUSTAINABILITY OF THE AQIQAH BUSINESS “GRUP TERNAK KITA” AMIDST MODERN MARKETING COMPETITION - Sinta Suci Lestari; Jojo Jojo; Gugyh Susandy; Devy Widya Apriandi; Asep Kurniawan; Mutqi Sopiawadi (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2025)
This research discusses the sustainability of business